Potential role of upadacitinib in cytomegalovirus colitis recurrence - Kaito Tsujinaka; Marina Kannno; Atsushi Ogawa; Kei Kawada; Mitsuhiro Goda; Hisanori Uehara; Keisuke Ishizawa (European Journal of Case Reports in Internal Medicine)
Background: Cytomegalovirus (CMV) colitis is a common complication in patients with ulcerative colitis (UC), which is often associated with immunosuppressive therapies including steroids, azathioprine, and biologics such as infliximab. Although CMV infections related to upadacitinib, a Janus kinase (JAK) inhibitor, have been reported, they typically occur after prolonged use. Consequently, early onset CMV colitis following the initiation of JAK inhibitors has not been extensively recognised. Case report: We present the case of a 68-year-old Japanese woman with refractory UC who developed CMV colitis that initially improved but worsened shortly after starting upadacitinib. The patient improved following upadacitinib discontinuation and CMV-specific treatment. This case suggests that early onset CMV colitis after upadacitinib initiation is clinically significant and highlights the importance of monitoring lymphocyte counts and CMV antigen levels during JAK inhibitor therapy. Conclusion: These findings provide valuable insights into the early risk of CMV reactivation and may guide future management strategies for patients with UC undergoing JAK inhibitor treatment.